2008
DOI: 10.4028/www.scientific.net/msf.607.177
|View full text |Cite
|
Sign up to set email alerts
|

Free Volumes in Polymer Nanocomposites

Abstract: We have employed positron annihilation lifetime spectroscopy to measure the free volumes in nanocomposites of polystyrene with addition of carbon nanofiber (CNF) and carbon dioxide as a function of composition and of temperature. We found that the glass transition temperature (Tg) increases as a function of CNF compositions but significantly decreases as the exposure of CO2. We also investigate the combination effect of CNF and CO2 and found that the CO2 significantly weakens the bonding between PS and CNF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…More common methods, such as NMR, FTIR, DMTA, neutron diffraction, X-ray diffraction, AFM, SEM, XPS, etc., have been employed to investigate polymer nanocomposites. Only recently, a novel method, positron annihilation spectroscopy (PAS), has been used to investigate atomic and molecular defects and interfacial properties. One of the PAS techniques, positron annihilation lifetime spectroscopy (PALS), is capable of determining the free-volume and hole properties directly at the atomic and nanoscale. , This capability arises from the fact that positronium (bound state of positron and electron; Ps) is preferentially localized in regions of low electron density sites, such as free volumes, holes, interfaces, and pores. The primary mechanism of annihilation of ortho positronium (o-Ps), the triplet state of Ps, is by pick-off with electrons of the polymeric materials under study.…”
Section: Introductionmentioning
confidence: 99%
“…More common methods, such as NMR, FTIR, DMTA, neutron diffraction, X-ray diffraction, AFM, SEM, XPS, etc., have been employed to investigate polymer nanocomposites. Only recently, a novel method, positron annihilation spectroscopy (PAS), has been used to investigate atomic and molecular defects and interfacial properties. One of the PAS techniques, positron annihilation lifetime spectroscopy (PALS), is capable of determining the free-volume and hole properties directly at the atomic and nanoscale. , This capability arises from the fact that positronium (bound state of positron and electron; Ps) is preferentially localized in regions of low electron density sites, such as free volumes, holes, interfaces, and pores. The primary mechanism of annihilation of ortho positronium (o-Ps), the triplet state of Ps, is by pick-off with electrons of the polymeric materials under study.…”
Section: Introductionmentioning
confidence: 99%
“…Glass transition temperature (T g ) of polymer nanocomposites, obtained by DSC, is related to the free volume of the polymer chains as described by the Williams-Landel-Ferry theory and the interaction strength between the polymer and particle interface [19,20]. Blum et al have studied how particle curvature, surface adsorption and composition influence the polymer-free volume observed as changes in glass transition temperature and deuterium nuclear magnetic resonance relaxation [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…However, in SiO 2 /PS nanocomposites, we found that τ 3 vs T could not be fitted well into simple two lines with low values of R 2 (correlation factors from fits < 0.94). This is very different from the case of strong interfacial bonding PS/CNF systems where single T g could be defined well by the intercept of two lines [8].…”
mentioning
confidence: 99%
“…However, the interactions between inorganic and its surrounding matrix material in such nanocomposite have yet been fully elucidated due to the limited method for determining the parameters controlling interfacial characteristics. Recently, we reported a study of positron annihilation lifetime study in a series of PS/CNF nanocomposites which have a strong interfacial interaction and found that T g increases as a function of wt% of CNF [8]. In this paper, we report the free volume and T g results of a study using positron annihilation lifetime in a weak interfacial interaction system, SiO 2 in PS as a function of temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation